1997
DOI: 10.1002/(sici)1098-2736(199702)34:2<101::aid-tea1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Guest editorial: Global science literacy: An earth system view

Abstract: During the summer of 1996, China, Korea, Bangladesh, India, and other Asian countries experienced very serious and deadly flooding. Over the past several years, the U.S. also has had extensive flooding around the Mississippi River and its tributaries as well as excessive summer temperatures, wild fires, and other destructive weather-related phenomena. In its report submitted in December 1995, the United Nations International Panel on Climate Change (IPCC) declared for the first time that "the balance of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…The goals of educating students for both environmental research and real-world problem solving are considered equally important and closely interconnected. Environmental research for sustainability is strongly problem driven and, therefore, not restricted to scientific inquiry and analysis; it has practical applications and is intended to serve society in solving real-world problems (Mayer, 1997). In particular, for urgent problems like climate change, ozone depletion, water scarcity, deforestation, and desertification, scientific research and mitigation efforts need to occur simultaneously.…”
Section: Goals and Didactics Of Environmental Science Education For Smentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of educating students for both environmental research and real-world problem solving are considered equally important and closely interconnected. Environmental research for sustainability is strongly problem driven and, therefore, not restricted to scientific inquiry and analysis; it has practical applications and is intended to serve society in solving real-world problems (Mayer, 1997). In particular, for urgent problems like climate change, ozone depletion, water scarcity, deforestation, and desertification, scientific research and mitigation efforts need to occur simultaneously.…”
Section: Goals and Didactics Of Environmental Science Education For Smentioning
confidence: 99%
“…Solving complex environmental problems requires a coherent and in-depth understanding of diverse natural systems and their interrelationships with each other and the anthroposphere. Mayer (1995Mayer ( , 1997 therefore suggests orienting environmental science education toward an Earth system approach that promotes an understanding of the whole world as one system and providing a system-oriented education in Earth's central subsystems-geosphere, hydrosphere, atmosphere, and biosphere (Ben-Zvi Assaraf & Orion, 2005). The myriad interactions between these spheres and human activities involve decision making related to human values and therefore require that the sociocultural and ethical context of environmental problems be considered.…”
mentioning
confidence: 99%
“…This was expanded into a proposal for a 'global science literacy' approach to the curriculum, based on the Earth system science (Mayer, 1995(Mayer, , 1997Mayer & Kumano, 1999;Mayer & Tokuyama, 2002). Strong arguments in support of this approach, used by Mayer and Kumano (1999), include: Figure 1.…”
mentioning
confidence: 99%
“…According to Mayer (1995), an earth systems science curricula requires that natural cycles and biogeochemical processes be studied in the context of environmental problems that affect students' everyday lives. Mayer (1997) later suggested that earth systems approach may provide a unifying framework for achieving global science literacy by encouraging "dialogue among peoples of different languages and different cultures" and a "sustainable lifestyle for all the world's citizens" (Mayer, 1997, p. 104). Investigating the role of humans in the earth systems requires an analysis of how people from different cultures understand and relate to nature.…”
Section: Nature---knowledge---culture Systemsmentioning
confidence: 99%